Neo-Victorian villains adaptations and transformations in popular culture - Poore, Benjamin 1971- (Brill Rodopi, 2017)
Neo-Victorian Villains' is the first edited collection to examine the afterlives of such Victorian villains as Dracula, Svengali, Dorian Gray and Jekyll and Hyde, exploring their representation in neo-Victorian drama and fiction. In addition, 'Neo-Victorian Villains' examines a number of villainous types, from the spirit medium and the femme fatale to the imperial 'native' and the ventriloquist, and traces their development from Victorian times through the twentieth century. Chapters analyse recent theatre, films and television - from 'Ripper Street' to Marvel superhero movies - as well as classic Hollywood depictions of the Victorian villains. In a wide-ranging opening chapter, Benjamin Poore assesses the legacy of nineteenth-century ideas of villains and villainy on the twentieth and twenty-first centuries. Contributors are: Sarah Artt, Guy Barefoot, Jonathan Buckmaster, David Bullen, Helen Davies, Robert Dean, Marion Gibson, Richard Hand, Emma James, Mark Jones, Emma V. Miller, Claire O'Callaghan, Christina Parker-Flynn, Frances Pheasant-Kelly, Natalie Russell, Gillian Piggott, Benjamin Poore and Rob Welch.
Keywords: Geschichte 1837-1901; Geschichte 1970-2015; Bösewicht; Kultur; Englisch; Literatur; Rezeption; Film; Großbritannien; Aufsatzsammlung